Comparison of Survival Between Irreversible Electroporation Followed by Chemotherapy and Chemotherapy Alone for Locally Advanced Pancreatic Cancer - He, Chaobin; Huang, Xin; Zhang, Yu; Cai, Zhiyuan; Lin, Xiaojun; Li, Shengping (Frontiers in Oncology, 2020)
Locally advanced pancreatic cancer (LAPC) has a dismal prognosis even after standard chemotherapy, and local progression contributes to nearly one-third of the deaths of these patients. As a local destructive method, irreversible electroporation (IRE) can feasibly treat LAPC. The aim of this study was to evaluate IRE combined with chemotherapy as a new treatment and compare its efficacy with that of chemotherapy alone in patients with LAPC. The data of LAPC patients who received chemotherapy with or without IRE were extracted from Surveillance, Epidemiology, and End Results (SEER) database and medical records of Sun Yat-sen University Cancer Center (SYSUCC). The efficacy of these two treatments was compared using propensity score matching (PSM) analysis. LAPC patients treated with the combination therapy had better overall survival (OS). Significantly higher cancer-specific survival (CSS) and progression-free survival (PFS) rates were also observed in patients after IRE combined with chemotherapy, compared with chemotherapy alone. IRE combined with chemotherapy was established as a favourable factor for OS, CSS, and PFS in LAPC patients. This combination method may be a more suitable treatment than chemotherapy alone for patients with LAPC.